1985
DOI: 10.1152/ajpendo.1985.249.4.e392
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of forskolin on LH and GH release

Abstract: The effects of forskolin, an agent which increases intracellular levels of cAMP, on basal luteinizing hormone (LH) and growth hormone (GH) release and on gonadotropin-releasing hormone (GnRH)-stimulated LH release were documented. Continuously perifused dispersed anterior pituitary cells from female rats at random stages of the estrous cycle were used. Secretory rates of both LH and GH increased in a concentration-dependent manner in response to a 1-h challenge with 0.03, 0.1, 0.3, 1, or 3 microM forskolin. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…1) was further evaluated in vitro for its SST-like activity. SST and its octapeptide analogs are known to inhibit the stimulated GH release from pituitary cells, induced by GH-RH (36) or adenylate-cyclase activator, forskolin (40) through receptor-mediated action. Thus, the GH-release inhibitory activities of AN-238 and carrier RC-121 were compared in superfused rat pituitary cell system.…”
Section: Discussionmentioning
confidence: 99%
“…1) was further evaluated in vitro for its SST-like activity. SST and its octapeptide analogs are known to inhibit the stimulated GH release from pituitary cells, induced by GH-RH (36) or adenylate-cyclase activator, forskolin (40) through receptor-mediated action. Thus, the GH-release inhibitory activities of AN-238 and carrier RC-121 were compared in superfused rat pituitary cell system.…”
Section: Discussionmentioning
confidence: 99%
“…A general consensus has been reached that cAMP does not participate in the acute release of LH in response to gonadotropin-releasing hormone (GnRH), but may rather affect the synthesis or post-translational processing of LH an d /o r in some manner interact with a secretory pathway such that LH becomes available for release upon proper signal ling [14], Consistent with the latter hypothesis, we have pre viously shown that an increase in intracellular cAMP induced by forskolin potentiates the amount of LH released after stimu lation by GnRH [15].…”
mentioning
confidence: 59%
“…Employing cholera toxin, forskolin and extracytoplasmic adenylate cyclase obtained from the Bordetellci pertussis organism, we found that both basal and GnRH-stimulated LH release is enhanced in the presence of increased cAMP production [26,27], In subsequent studies using cells in a continuous perifusion system, we found that the release of LH is delayed and gradual following application of probes known to enhance cAMP production immediately in contrast to the brisk, immediate rise which occurs in response to GnRH [15]. Taken together, these investigations confirmed a relationship between cAMP and LH secretion separate from any effect on the GnRH receptor and suggested that the failure of some investigators to document this relationship may be at tributable to the experimental time course required to detect the cAMP effect.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In H295R cells, forskolin up‐regulated the levels of aromatase and sex hormones as previous study (OECD, 2022; Watanabe & Nakajin, 2004). Forskolin increased luteinizing hormone and growth hormone (Evans et al, 1985), and consequently induced the expression of steroidogenesis‐related enzymes via the accumulation of cAMP in the sex hormone‐producing organs, such as adrenal and ovary (Jefcoate et al, 2011; Watanabe & Nakajin, 2004; Lehmann et al, 2005).…”
Section: Discussionmentioning
confidence: 99%